Outcomes of Single-Level and Multi-Level Thoracoscopic Sympathectomy in Primary Axillary Hyperhidrosis: A Multicenter Retrospective Analysis - Özer, Erhan; Güneş, Hayriye; Ekim, Teoman; Melek, Hüseyin; Bayram, Ahmet Sami; Gebitekin, Cengiz (The European Research Journal, 2026)
Objective: Primary axillary hyperhidrosis is associated with substantial impairment in quality of life, and endoscopic thoracic sympathectomy (ETS) provides definitive treatment in refractory cases. However, the optimal level of sympathetic interruption remains controversial, and evidence directly comparing different surgical levels in axillary disease is limited. This study aimed to compare surgical outcomes among three sympathectomy levels in patients with primary axillary hyperhidrosis. Methods: This retrospective multicenter study included 83 patients who underwent bilateral clip-based thoracoscopic sympathectomy for primary axillary hyperhidrosis between 2009 and 2023. Patients were stratified into three groups: single-level R3 (n=24), single-level R4 (n=35), and multi-level R2–R4 (n=24). The primary outcome was compensatory hyperhidrosis. Secondary outcomes included complete remission, recurrence, postoperative complications, and patient satisfaction. Factors associated with outcomes were evaluated using univariate and multivariate logistic regression analyses. Results: Compensatory hyperhidrosis occurred in 83.3% of patients in the R2–R4 group, compared with 75.0% in the R3 group and 54.3% in the R4 group (P=0.045). Complete remission rates were comparable among groups (54.2%, 41.7%, and 34.3%, respectively; P=0.452). In multivariate analysis, R4 sympathectomy was associated with significantly lower odds ratio (OR) of compensatory hyperhidrosis compared with R2–R4 (OR: 0.25, 95% CI: 0.06–0.97; P=0.044). Recurrence rates did not differ significantly among groups (20.8%, 25.7%, and 12.5%, respectively; P=0.466). Recurrence was the only independent predictor of patient dissatisfaction (OR: 0.12, 95% CI: 0.03–0.44; P=0.001). Conclusion: Single-level R4 sympathectomy appears to provide a favorable balance between treatment efficacy and side-effect profile in primary axillary hyperhidrosis. Multi-level approaches were not associated with improved clinical outcomes but were linked to higher rates of compensatory hyperhidrosis. These findings should be interpreted with caution.